2010
DOI: 10.1016/j.nurt.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Calpain as a Therapeutic Target in Traumatic Brain Injury

Abstract: Summary:The family of calcium-activated neutral proteases, calpains, appears to play a key role in neuropathologic events following traumatic brain injury (TBI). Neuronal calpain activation has been observed within minutes to hours after either contusive or diffuse brain trauma in animals, suggesting that calpains are an early mediator of neuronal damage. Whereas transient calpain activation triggers numerous cell signaling and remodeling events involved in normal physiological processes, the sustained calpain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
146
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 95 publications
2
146
0
Order By: Relevance
“…These data suggest that E64d may have some off-target effects during early post-trauma. A likely offtarget candidate may be inhibition of the calpains, which are known TBI drug targets, 43 because calpain-1 KO studies have validated as such. 44 Brain calpain activity spikes within 24 h of trauma, [45][46][47] and E64d administration has been shown to reduce calpain activity and provide neuroprotection after trauma.…”
Section: E64d Improves Traumatic Brain Injurymentioning
confidence: 99%
“…These data suggest that E64d may have some off-target effects during early post-trauma. A likely offtarget candidate may be inhibition of the calpains, which are known TBI drug targets, 43 because calpain-1 KO studies have validated as such. 44 Brain calpain activity spikes within 24 h of trauma, [45][46][47] and E64d administration has been shown to reduce calpain activity and provide neuroprotection after trauma.…”
Section: E64d Improves Traumatic Brain Injurymentioning
confidence: 99%
“…It is believed that post-traumatic calpain activity within axons contributes to transport disruption, cytoskeletal degradation, and subsequent axotomy. However, there is also robust calpain activity in neuronal somata and dendrites after TBI (Saatman et al, 2010). Trying to measure the role of axonal calpains in whole brain TBI models is complex because many supra-axonal structures are affected.…”
Section: Introductionmentioning
confidence: 99%
“…CNJ-328, and then, in 2013, we reported an additional 14 thalassospiramides from Thalassospira and Tistrella strains. We found that many of these compounds display a high inhibitive potency (nanomolar levels) of human calpain protease (4), a calcium-dependent enzyme family implicated in neurological disorders (5), muscular dystrophies, cortical cataracts (6), and cancer (7). For example, inflammatory cytokines that lead to neuronal network disruption, increase intracellular calcium, and increase calpain protease activity are a possible trigger for Alzheimer's disease (8).…”
mentioning
confidence: 99%